Municipally owned companies as executors of tasks pertaining to municipal waste management - Famielec, Józefa; Famielec, Stanisław Jakub (Journal of Public Governance, 2019)
Objectives: Services provided in the general economic interest constitute a fairly significant research field with regard to public management, involving different local governing tasks, including municipal waste management. Full management of municipal waste services is carried out by individual municipalities (from July 2013 onwards), therefore the purpose of the article is pinpointing the municipal waste management providers (Municipally Owned Companies) in Polish provincial cities, including those using the in-house model.Research Design & Methods: The process of identifying the entities engaged in waste management as municipally owned companies (referred hereafter as “MOCs”) is preceded by a theoretical analysis of the peculiarities of municipal waste and municipal waste management, both of which are regarded as crucial and having imminent economic and social consequences. During that theoretical analysis the authors applied the European Union hierarchy on waste management in establishing the following waste management criteria: achieving of a specified rate of recovery and recycling; standardisation of the magnitude and structure of waste flows directed to incineration plants and landfill; and comprehensiveness of the waste management system.Findings: It has been established that MOCs (including those operating via in-house orders) are the principal type of entities which provide municipal waste management services in the cities included in the analysis.Implications / Recommendations: The article shows a clear need for further research on the efficiency of MOCs regarding the provision and performance of public utility services and tasks.Contribution / Value Added: The conducted research provides evidence supporting the statement that municipal waste management is performed mostly by MOCs, which are entrusted with public utility tasks through tender procedures or, more frequently, via in-house orders. Such entities co-operate with the private sector, with private sector firms often owning specialised installations.